AB0724 DOSE PREGNANCY AND VAGINAL DELIVERY WORSEN ANKYLOSING SPONDYLITIS?. (June 2019) - Lee, Jung Sun; Oh, Ji Seon; Seo, Wook Jang; Hong, Seokchan; Kim, Yong-Gil; Lee, Chang-Keun; Yoo, Bin
Abstract : Background: Ankylosing spondylitis (AS) affects the sacroiliac joints and commonly occurs in those at the reproductive age. Women with aS have a higher rate of cesarean section (CS) compared with healthy controls. Objectives: This study determined the effect of pregnancy and delivery methods on aS worsening by analyzing prescription pattern. Methods: Based on the Korean Health insurance Review and assessment Service claims database, subjects comprised female patients aged 20–49 years with an aS. Alteration of prescriptions was defined by changing the at two time periods of 1–2 years pre-delivery and 1-year post-delivery. We compared alteration of prescriptions between aS patients with delivery and 1:1 matched aS patients without delivery. In addition, among aS patients with delivery, alteration of prescriptions according to delivery method was evaluated. Results: Among 6, 821 female patients with aS, 996 patients in the delivery group were younger, had a higher proportion of non-drug use, and had lower rates of comorbidity than the no delivery group. The alteration of prescriptions did not differ between the aS with delivery and the aS without delivery groups (OR 0.76, 95% CI 0.56–1.05). Furthermore, the overall alteration of prescriptions did not differ significantly between vaginal delivery (VD) and CS (OR 0.72, 95% CI 0.45–1.14). Conclusion: The rate of alteration of prescriptions was comparable between the aS patients with and without delivery. There was no association between VD and alteration of prescriptions compared with CS. Taken together, pregnancy and VD may not be assumed to be factors of aS worsening. Disclosure of interests: None declared